Circulation patterns identified by spatial rainfall and ocean wave fields in Southern Africa - Bárdossy, András; Pegram, Geoffrey; Sinclair, Scott; Pringle, Justin; Stretch, Derek (Frontiers in Environmental Science, 2015)
This paper presents the application of Fuzzy Rule Based Circulation Patterns (CPs) classification in the description and modeling of two different physical processes: rainfall regimes and ocean waves. Large ocean waves are typically generated over fetches of the order of thousands of kilometers far off shore, whereas rainfall is generated by local atmospheric variables including temperature, humidity, wind speed, and radiation over the area of concern. The spatial distribution of these variables is strongly dependent on regional pressure patterns, which are similar for associated weather and wind behavior on a given day. The choice of the CP groupings is made by searching for those CPs which generate (i) different daily rainfall patterns over mesoscale regions and (ii) wave heights from different directions at chosen shoreline locations. The method used to choose the groupings of CPs is a bottom-up methodology using simulated annealing, ensuring that the causative CPs are responsible for the character of the results. This approach is in marked distinction to top-down approaches such as k-means clustering or Self Organizing Maps (SOMS) to identify several classes of CPs and then analysing the effects of those CPs on the variables of choice on given historical days. The CP groups we define are often different for the two phenomena (rainfall and waves) simply because different details of the pressure fields are responsible for wind and for precipitation. The region chosen for the application is the province of KwaZulu-Natal in South Africa, using the same set of raw geopotential heights to represent the pressure patterns, but selecting from the set those typical patterns affecting ocean waves on the one hand and regional rainfall on the other.